การปรับตัวของนิทานก้อมบนยูทูบ - วีรภัทร บุญมา (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This research aims to study the adaptation of Nithan Gom Short Fables on YouTube and the changes in their creative process on digital media since the time of oral literature, VCD and a new media, YouTube, regarding both format and content using qualitative study approach. Divided into two sections, content analysis and in-depth interviews. Content analysis part uses 30 most-watched Nithan Gom Short Fables on YouTube from 3 artists: 1) Si Kanso, using only single voice dubbing format, 2) Chanchoi Lompadpai, using both narrative dubbing and actors dubbing technique, and 3) Taker Audio, using actors dubbing only, and the latter is conducted with the three aforementioned Nithan Gom Short Fables creators. From 30 samples, from presentation aspect, all three artists are different on sound usage despite their similarity on setting where they usually employed wooden house with lifting basement. Each artist’s works prefer a conventional plot over a contemporary plot, and all characters are of North Eastern region (E-San), speaking their local language (E-San) with agrarian background. The most popular content appeared on Nithan Gom Short Fables are sexuality and foolishness and cleverness, respectively. Si Kanso uses YouTube as a channel to distribute behind-the-scene clips while adopting positive attitude that such new media enhances the distribution of VCD. Chanchoi Lompadpai uses YouTube channel to broadcast works that have VCD copy rights and to interact with audience. He perceives that a new media reduces both production and distribution costs and overcomes the physical space. Taker Audio, by far, has adapted the most as he ceased VCD production completely and uses YouTube as a sole distribution channel. While the artist takes this opportunity to communicate with audience through comment boxes, the decrease on income is inevitable. He also thinks that technological change in current media takes place rather rapidly.